AN ANALYSIS OF TRANSLATION DIFFICULTIES ON BARRACK OBAMAâ€™S SPEECH TEXT AT SIXTH SEMESTER STUDENTS OF MUHAMMADIYAH UNIVERSITY OF TANGERANG - Gunawan, Yudhie Indra; -, Nasrul Hasan; Firdaus, Moh Iqbal (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
English is international language that used by people in this world to get something like knowledge, information, and communication. In Indonesia, English used as school subject because English is important to studentsâ€™ future in their careers, especially interaction with foreigner, because in Indonesia many interesting destination for foreigner, media and technology use English to inform the information or knowledge. Those are reasons, Indonesian must be able to understand English especially in words meaning in English, because translation is important to know information which use English media. ). For this research, the researchers use descriptive analysis research. The researchers directly find accurate data of difficulties in translating from source language into target language or SL into TL. The researchers have got studentsâ€™ test result, based on the result it shows that the students still confuse to convey the meaning from source language, the students translate the text word by word and the meaning not deliver, and the researchers have got studentsâ€™ test result, based on the result it shows that the students could not to use equivalent, they still lack of vocabulary mastery, they could not translate the sentence, because in English one word has many meaning, and confuse how to use equivalent words in translation that they states from interview â€œi still lack of vocabulary masteryâ€ and â€œin English one word many meaning thus we could not translate the sentence because depend on the topicâ€.